2016
DOI: 10.1111/jocn.13125
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical factors affecting body image, sexual function and sexual satisfaction in women with breast cancer

Abstract: A well-trained multidisciplinary team should be available to evaluate women's need for support and to provide information on the disease, its treatment and its impact on their lives and on their sexuality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
2
17
3
Order By: Relevance
“…After cancer, the majority of women in this study (70.2%) confirmed that they continued to have sexual activity, with is consistent with the literature [14, 15, 16]. Although the frequency of sexual relations is lower after cancer, 60.7% reported that they have sexual relationships 1–2 times per month [5, 9, 12, 16].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…After cancer, the majority of women in this study (70.2%) confirmed that they continued to have sexual activity, with is consistent with the literature [14, 15, 16]. Although the frequency of sexual relations is lower after cancer, 60.7% reported that they have sexual relationships 1–2 times per month [5, 9, 12, 16].…”
Section: Discussionsupporting
confidence: 90%
“…After breast cancer, 91.2% reported that they had some type of sexual difficulty. This incidence is higher than other studies, where it was found to vary from 40 to 80% [5, 6, 9, 13, 14]. This could be because women participating in this study were young; the average age was 46.34-years-old.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, the incidence rate is expected to grow rapidly in the next few years simply due to the aging of the population and the greater adoption of a Western lifestyle by the Turkish population [4]. Along with their function in feeding infants, female breasts permanently impact a woman's perception of her body image [5]. Mastectomy, as a breast removal, is commonly associated with loss of this worthy image because it involves the removal of an organ that women consider symbolic of their femininity and sexuality [6].…”
Section: Introductionmentioning
confidence: 99%